Effect of feeding Tephrosia bracteolate on the bioavailability of macro minerals in goat (Bangladesh Journal of Animal Science, 2021)
Sixteen West African Dwarf Goats (8 bucks and 8 does) were balanced for age, sex and weight (average of 5.79±0.60 kg), to evaluate the effect of Tephrosia bracteolata (Tb) on macro mineral utilization. To examine the effect of Tephrosia bracteolata (Tb), different levels of Tb were used (Tb20, Tb40, Tb60 and Tb80). Ca absorbed (gm) ranged from 0.64 (Tb20) to 1.57 (Tb80) and Ca retention was from 0.62 (Tb20) to 1.56 (Tb80) which was partially linear. In both absorption and retention of Ca, Tb20 and Tb80 found the lowest (P